Graphene derivative based high dielectric constant polymer composite electrodes for supercapacitors. (2021) - Srivastava, Nisha; Patodia, Tarun; Yadav, Anju; Yadav, Dinesh; Jakhar, Narendra; Sharma, K.B.; Tripathi, Balram
Abstract: Graphene oxide (GO) and reduced graphene oxide (rGO) based polyvinylidene fluoride (PVDF) flexible composites were prepared using GO and rGO fillers in PVDF matrix by solution casting method. These composites were characterized with X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, Impedance analyzer (dielectric constant) and Field emission electron microscopy (FE-SEM). The dielectric constants at 1 MHz frequency for PVDF, 5%GO/PVDF and 5% rGO/PVDF composites were obtained 3.68, 12.20 & 30.32 respectively, ascribed to Maxwell-Wagner-Sillars (MWS) polarization mechanism and the exchange coupling at the surface and interface. According to MWS polarization charges could be accumulated at the interface when an external field was acted on composites due to heterogeneous response of GO, rGO and PVDF attributed alternate of electrode materials for superacapacitors.